2017
DOI: 10.1371/journal.pone.0188454
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab potentially prevents bone loss in patients with anticitrullinated protein antibody-positive rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is associated with a high risk of osteoporosis and fracture. Interleukin (IL)-6 inhibitors may suppress osteoclast activation. Anticitrullinated protein antibody (ACPA) titers are inversely associated with bone mineral density (BMD). However, the differential effect of ACPA on bone turnover marker (BTM) and BMD changes after IL-6 inhibition remains unclear. This prospective study recruited patients with active RA with inadequate response to methotrexate or biologics. BMD was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 37 publications
1
23
0
3
Order By: Relevance
“…Indeed, they found that IL-6 blockade reduced bone erosion in TNF-α transgenic murine models through a direct effect on osteoclast activity which was independent from the anti-inflammatory action ( 61 ). Other studies on human subjects further confirmed the positive effect of tocilizumab on bone erosions ( 62 ) and systemic bone loss, especially in ACPA positive patients ( 52 , 63 ).…”
Section: Rheumatoid Arthritismentioning
confidence: 61%
“…Indeed, they found that IL-6 blockade reduced bone erosion in TNF-α transgenic murine models through a direct effect on osteoclast activity which was independent from the anti-inflammatory action ( 61 ). Other studies on human subjects further confirmed the positive effect of tocilizumab on bone erosions ( 62 ) and systemic bone loss, especially in ACPA positive patients ( 52 , 63 ).…”
Section: Rheumatoid Arthritismentioning
confidence: 61%
“…Kume et al showed the improvement effect on bone mineral density (BMD) in patients with RA treated with tocilizumab [ 23 ]. Furthermore, Chen et al showed the decrease of the bone resorption marker and BMD improvement with tocilizumab treatment [ 24 ]. These anti-bone resorption effects of tocilizumab may explain the repairing effect of the large geode.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL‐6 is one of the key cytokine effectors of the tissue response in RA , also having important effects on the production of antibodies by B cells . It was showed that IL‐6 inhibition in ACPA‐seropositive patients reduced bone loss, demonstrating that IL‐6 have a negative impact on bone metabolism in the presence of ACPAs .…”
Section: Discussionmentioning
confidence: 99%